Individual performance review in hospital practice: the development of a framework and evaluation of doctors' attitudes to its value and implementation. Issue 11 (8th June 2013) - Trebble, T M; Cruickshank, L; Hockey, P M; Heyworth, N; Powell, T; Clarke, N
Abstract : Background: Appraisal, or independent performance review (IPR) is used in human resources management in the commercial and public sectors to evaluate the performance of an employee against agreed local organisational expectations and objectives, and to identify their requirements for development and effective management. IPR for NHS consultants may provide essential information for job planning, contribute towards medical appraisal for revalidation, and facilitate productivity and quality improvement. Aims: To develop a framework for IPR for consultants, and to determine attitudes on its value, process and content. Method: Information from commercial, public and voluntary sector models and published and other literature sources were used to develop an IPR framework. This was assessed through a three-cycle action research methodology involving qualitative interviews with 22 consultants (predominantly with medical management roles). Results: The domains of the IPR framework included: (1) performance against objectives; (2) behaviour and leadership; (3) talent management; (4) agreed future objectives. A number of themes were identified from the consultant interviews including: ineffective current appraisal systems reflecting a lack of valid performance data and allotted time; a lack of empowerment of medical managers to address performance issues; IPR as a more explicit system, offering value in evaluating doctors performance; and the dependence of successful implementation on the engagement of the Trust executive. Conclusions: IPR may have value for performance evaluation of consultants, contributing toward job planning and complementing medical appraisal. Support by their employing organisation and engagement with medical managers in design and implementation is likely to be essential.